Incidence of venous thromboembolism following major surgery in Korea: from the Health Insurance Review and Assessment Service database. (27th June 2014) - Yhim, H.‐Y.; Jang, M.‐J.; Bang, S.‐M.; Kim, K. H.; Kim, Y.‐K.; Nam, S.‐H.; Bae, S. H.; Kim, S.‐H.; Mun, Y.‐C.; Kim, I.; Jung, C. W.; Oh, D.
Summary Background Data on the incidence of venous thromboembolism (VTE) following major surgery in Asian populations are limited. Methods Using the Korean Health Insurance Review and Assessment Service database, we performed a nationwide population‐based epidemiologic study to estimate the incidence of VTE after major orthopedic, cancer, and benign surgeries. VTE cases were identified from all patients undergoing major surgery between 2007 and 2011 using both diagnostic and drug codes as treatment evidence of VTE within 5 weeks of surgery. We also calculated the relative risk of VTE in major orthopedic and cancer surgery compared to benign surgery. Results The overall rates of postoperative VTE were 1.24%, 0.67%, and 0.05% for major orthopedic, cancer, and benign surgeries, respectively. Hip fracture (1.60%) and colorectal cancer surgeries (1.67%) were associated with the highest rates of VTE, and the rates steadily increased during the study period. Advanced age, female sex, and general anesthesia were independent risk factors for VTE. Patients undergoing surgery for colorectal, pancreatic, ovarian, and esophageal cancer, and major orthopedic surgery had a > 20‐fold higher risk of VTE than those undergoing benign surgery. Conclusions This is the largest epidemiologic study to investigate the incidence of VTE after major surgery in Asia, demonstrating that the rates of postoperative VTE are lower than in Caucasian populations. This study contributes to a better understanding of the differences in postoperative VTE development between Korean and Caucasian populations; the data also suggest that perioperative prophylactic strategies in Asians should be based on studies of such populations.